Respostas

2014-07-14T22:52:02-03:00
4x² + 4x + 1 = 0
a = 4
b = 4
c = 1
      Δ = b² - 4ac
      Δ = 4² - 4 * 4 * 1
      Δ = 16 - 16
      Δ = 0
             x =  - b ± √Δ  
                        2a
             x =  - 4 ± √0 
                      2 * 4
             x' =  - 4 - 0  =  - 4  =  - 2  =  - 1 
                        8          8        4        2
             x'' =  - 4 + 0  =  - 4  =  - 2 =  - 1       
                         8          8        4        2

Como o delta (Δ) é igual a zero, as raízes da equação serão iguais, neste caso -1/2.

Espero ter ajudado. Valeu! 
2014-07-14T22:55:02-03:00
4x² + 4x + 1 = 0a = 4b = 4c = 1      Δ = b² - 4ac      Δ = 4² - 4 * 4 * 1      Δ = 16 - 16      Δ = 0             x =  - b ± √Δ                          2a             x =  - 4 ± √0                       2 * 4             x' =  - 4 - 0  =  - 4  =  - 2  =  - 1                         8          8        4        2             x'' =  - 4 + 0  =  - 4  =  - 2 =  - 1                                8          8        4        2
Como o delta (Δ) é igual a zero, as raízes da equação serão iguais, neste caso -1/2.